Concordance of self-reported varicella history and serology among adolescent and adult refugee patients at a primary care clinic in Toronto, Canada. Issue 43 (15th October 2021) - Müller, Frank; Chandra, Shivani; Wright, Vanessa; Rashid, Meb; Redditt, Vanessa
Abstract: Background: Previous studies have found higher rates of varicella susceptibility among migrants from tropical regions. This study seeks to estimate the prevalence of varicella susceptibility in a cohort of newly arrived refugees and refugee claimants at a primary care clinic in Toronto and to compare patients' self-reported history of varicella infection with serologic test results. Methods: We conducted a retrospective chart review of 1888 refugee patients aged 13 years and older rostered at a specialized primary care clinic in Toronto from December 2011 to October 2017. Basic sociodemographic variables, self-reported varicella history, and varicella serologic results were examined. Results: Based on serologic testing, 8.5% of individuals were varicella non-immune, with highest rates of varicella susceptibility among adolescents aged 13–19 years (13.5%). All adults over age 60 were varicella immune on serology (n = 56). A positive self-reported history of varicella infection was strongly predictive of varicella immunity on serology (PPV 96.8%; 95% CI: 95.2–97.9). A self-reported history of no prior varicella infection did not correlate reliably with serologic test results (NPV 15.8%; 95% CI: 13.3–18.0). A substantial proportion of patients (34.1%) were unsure of their varicella history. Conclusion: Identification and immunization of varicella susceptible refugee newcomers remains a health care priority. Self-reported history of varicella infection had mixed reliability as a predictor of varicella immunity.